(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Bioanalytical methods play a critical role in the pharmaceutical industry, providing essential tools for drug development, pharmacokinetics, and therapeutic drug monitoring. This review discusses the principles of bioanalytical method development and validation, highlighting key techniques such as chromatography, mass spectrometry, and immunoassays. It further explores the applications of these methods in various areas of pharmacy, including drug formulation, clinical trials, and personalized medicine. Challenges and future directions in bioanalytical method development are also addressed.